Retrospective evaluation of frozen section use for thyroid nodules with a prior fine needle aspiration diagnosis of Bethesda IIâVI: The Weill Cornell Medical College experience - Marc A. Cohen (KeAi Communications Co., Ltd., 2015)
Objective: To evaluate the Weill Cornell Medical College (WCMC)/New York Presbyterian Hospital (NYPH) experience with intraoperative frozen (IOF) section in the management of thyroid nodules with a fine needle aspiration (FNA) diagnosis of Bethesda IIâVI and to analyze the cost and pathology benefit it provides. Methods: The surgical and cytopathology files at WCMC/NYPH were searched within the time period of January 2008 to May 2013. A total of 435 thyroid specimens were identified for which both an FNA and subsequent IOF section was performed. The FNA was correlated with the locations of the resected nodule and the nodule frozen for intraoperative diagnosis. The results of the FNA were compared to the IOF section diagnosis and final diagnosis (FD). Results: Among 435 cases, the FNA diagnosis was Bethesda II: 149 cases, Bethesda III: 170 cases, Bethesda IV: 91 cases, Bethesda V: 19 cases, and Bethesda VI: 6 cases. There were a total of 83 carcinomas identified on FD, which included 69 papillary thyroid carcinomas (PTCs), 12 follicular carcinomas, and 2 poorly differentiated carcinomas. The preoperative FNA diagnosis for these carcinomas was as follows: Bethesda II, 11/149 (7.4%), Bethesda III, 24/170 (14%), Bethesda IV, 26/91 (29%), Bethesda V, 16/19 (84%), and Bethesda VI, 6/6Â (100%). IOF section contributed to the diagnosis of malignancy in 16/429 (4%) cases: 1/149 (0.7%) Bethesda II, 5/170 (3%) Bethesda III, 2/91 (1.1%) Bethesda IV, and 8/19 (42%) Bethesda V. The diagnosis of malignancy was confirmed in the 6 Bethesda VI cases by IOF section. There were no false positives on IOF section. IOF had a sensitivity and specificity of 26% and 100%, respectively. Conclusion: The role of IOF section is limited in the evaluation of thyroid nodules. IOF section is most useful for nodules with an FNA diagnosis of Bethesda V lesions. The diagnosis of follicular variant of PTC remains difficult on frozen section. Keywords: Thyroid, Nodule, Frozen section, Fine-needle aspiration, Sensitivity, Specificity